(untitled) (Journal of Medical & Health Sciences Review, 2025)
The functional foods, that provide a range of health benefits in addition to nutrition, are becoming a recognized concept in the global market, as there are more people concerned about the connection between foods and health. It is in this review that the potential power of nanotechnology in the progression of functional foods is discussed as involving the interface between microbiology and material science. On the scale of 1-100 nm, nanotechnology can be used to give materials new and desirable physicochemical characteristics that are used in new applications throughout the food chain. It also greatly enhances the sensitivity bioavailability and targeted delivery of bioactive compounds which can be vitamins, minerals and antioxidants by protecting the active product against degradation, enhancing its solubility and absorption in the gastrointestinal tract. In addition to this, the nano-enabled systems provide effective shield around the probiotics to deter triggering of their adverse reactions towards the harsh environments in the stomach region, hence enhancing their survivability and effective delivery to the gut where they can be used to metabolize the microbiota effectively. The role of material science in progress with this is in the design and manufacturing of advanced nanoconstructed nanocarriers comprised of food-grade biopolymeric materials (e.g., proteins, lipids, polysaccharides) that are able to control the release as well as be stimuli responsive through the active agent. At the same time, nanosensors, a product of the material science are transforming the quality and safety of foods within the foods sector by real-time monitoring of freshness, spoilage, pathogens, and nutrient values. Although these are enormous advantages, there remain major problems as it pertains to whether the engineered nanoparticles can be toxic and bio accumulative in the human body and within the food chain. There are also challenges in the form of regulatory landscape which is changing and the higher consumer acceptance which is needed. Future prospects are highlighted towards further interdisciplinary studies especially in synthetic biology, 3D food printing and multi-omics strategies to open up a new era of personalized nutrition as well as sustainable food systems. The combination will bring high specificity, efficiency, and safety in the applications of functional foods to solve nutritional and health issues around the world.